Markers of acute toxicity of DDT exposure in pancreatic beta-cells determined by a proteomic approach - Pavlikova, Nela; Sramek, Jan; Jelinek, Michael; Halada, Petr; Kovar, Jan (PloS one, 2020)
Many compounds have the potential to harm pancreatic beta-cells; organochlorine pollutants belong to those compounds. In this work, we aimed to find markers of acute toxicity of p,p'-DDT exposure among proteins expressed in NES2Y human pancreatic beta-cells employing 2-D electrophoresis. We exposed NES2Y cells to a high concentration (150 μM, LC96 after 72 hours) of p,p'-DDT for 24 and 30 hours and determined proteins with changed expression using 2-D electrophoresis. We have found 22 proteins that changed their expression. They included proteins involved in ER stress (GRP78, and endoplasmin), mitochondrial proteins (GRP75, ECHM, IDH3A, NDUS1, and NDUS3), proteins involved in the maintenance of the cell morphology (EFHD2, TCPA, NDRG1, and ezrin), and some other proteins (HNRPF, HNRH1, K2C8, vimentin, PBDC1, EF2, PCNA, biliverdin reductase, G3BP1, FRIL, and HSP27). The proteins we have identified may serve as indicators of p,p'-DDT toxicity in beta-cells in future studies, including long-term exposure to environmentally relevant concentrations.
Keywords: beta-buňky; Cell Line; proteomika; Gene Expression Regulation; Electrophoresis, Gel, Two-Dimensional; Mass Spectrometry; chaperon endoplazmatického retikula BiP; regulace genové exprese; Proteomics; Humans; Endoplasmic Reticulum Chaperone BiP; biologické markery; 2D gelová elektroforéza; DDT; Insulin-Secreting Cells; viabilita buněk; Cell Survival; buněčné linie; Biomarkers; hmotnostní spektrometrie; lidé